OPINI PUBLIK DALAM SISTEM DEMOKRASI - Serliana; Haura Putri Aqillah; Desi Ratna Sari Lumban Gaol; Mhd Rafi Zhafran (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
Public opinion is a crucial element in a democratic system, serving as a reflection of the public's views on political issues and government policies. This study analyzes the relationship between elections and public opinion, as well as the influence of polling on opinion formation and political legitimacy. Using qualitative research methods, this study finds that elections are a vehicle for the public to express their aspirations, while public opinion acts as a social control that influences government policies. Polling results not only measure support for candidates but also shape voter behavior. In addition, strong public opinion can increase government legitimacy, while ignoring the voice of the people has the potential to cause political instability. This study concludes that active public involvement in the political process is essential to creating an accountable and responsive government.